What do hearing healthcare professionals do to promote hearing aid use and benefit among adults? A systematic review - Ismail, Noor Afzarini Hasnita; Kevin J, Munro; Armitage, Christopher J.; Dawes, Piers (Taylor & Francis, 2019)
Objective: To conduct a systematic review of the evidence in relation to what hearing healthcare professionals do during hearing aid consultations and identifying which behaviours promote hearing aid use and benefit among adult patients. Design: Searches were performed in electronic databases MEDLINE, EMBASE, CINAHL, PsycInfo, Web of Science, PubMed and Google Scholar. The Crowe Critical Appraisal Tool and Melnyk Levels of Evidence were used to assess quality and level of evidence of eligible studies. Behaviours of hearing healthcare professionals were summarised descriptively. Study Sample: 17 studies met the inclusion criteria. Results: Twelve studies described behaviours of audiologists and five studies were intervention studies. Audiologists were typically task- or technically-oriented and/or dominated the interaction during hearing aid consultations. Two intervention studies suggested that use of motivational interviewing techniques by audiologists may increase hearing aid use in patients. Conclusions: Most studies of clinicians’ behaviours were descriptive, with very little research linking clinician behaviour to patient outcomes. The present review sets the research agenda for better-controlled intervention studies to identify which clinician behaviours better promote patient hearing aid outcomes and develop an evidence base for best clinical practice.